Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1097/smj.0b013e318151fba4
|View full text |Cite
|
Sign up to set email alerts
|

Purple Urine Bag Syndrome: A Rare and Interesting Phenomenon

Abstract: Discoloration of urine is not uncommonly encountered in clinical practice and may indicate a significant pathology. However, the majority of instances are benign and occur as the result of trauma to the urological system during procedures or ingestions of substances such as medication or food. Purple discoloration of a urinary catheter bag is rare and can be alarming to both patients and healthcare workers. This phenomenon is known as the purple urine bag syndrome. It is associated with urinary tract infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 9 publications
0
20
0
7
Order By: Relevance
“…This is excreted and in the urine broken down by bacteria possessing one or both enzymes, sulphatase and phosphatase that metabolize this pigment to indirubin and indigo in an alkaline environment (urine). The indigo can also be precipitate in the catheter itself giving a blue discoloration (Harun et al 2007). In this paper, we found that PUBS seemed to have a higher incidence in patients with a bedridden status, alkaline urine, and species of bacteria with indoxyl sulphatase/phosphatase, but possibly not associated with gender, constipation, or type of PVC urine bag used.…”
Section: Resultsmentioning
confidence: 56%
“…This is excreted and in the urine broken down by bacteria possessing one or both enzymes, sulphatase and phosphatase that metabolize this pigment to indirubin and indigo in an alkaline environment (urine). The indigo can also be precipitate in the catheter itself giving a blue discoloration (Harun et al 2007). In this paper, we found that PUBS seemed to have a higher incidence in patients with a bedridden status, alkaline urine, and species of bacteria with indoxyl sulphatase/phosphatase, but possibly not associated with gender, constipation, or type of PVC urine bag used.…”
Section: Resultsmentioning
confidence: 56%
“…Bien que rares, les publications sur ce sujet sont périodiques, surtout depuis 2005, mais concernent le plus souvent un ou deux cas [2][3][4][5][6][7][8][9][10][11][12], rarement un nombre supérieur à cinq [13][14][15]. Seules deux publications font état de plus de dix cas [16][17].…”
Section: Discussionunclassified
“…6 Additionally, only a portion of each bacterial species listed above carries indoxyl phosphatase and sulphatase enzymes, as they are not ubiquitously found. 7 A number of conditions may cause urine discoloration, producing a variety of abnormal colors. For example, red and orange urine may be caused by medications like Rifampin, Warfarin, Isoniazid, and Sulfasalazine, medical conditions producing intravascular hemolysis like hemolytic anemia, thalassemia, and transfusion reactions, other medical conditions like nephrolithiasis and porphyria, and foods like beets and carrots.…”
Section: Discussionmentioning
confidence: 99%